Pressure-sensitive adhesive composition

A pressure-sensitive adhesive composition with alkoxyalkyl acrylate monomer and water-absorbing material addresses the challenge of adhesion and releasability on wet, uneven surfaces, providing effective temporary protection.

JP7628012B2Active Publication Date: 2025-02-07NIPPON SHOKUBAI CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020183085
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-30
Publication Date
2025-02-07
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

Existing adhesive compositions struggle to provide both strong adhesion and releasability on wet surfaces, particularly those with unevenness, such as concrete or mortar surfaces.

Method used

A pressure-sensitive adhesive composition containing a polymer with structural units derived from alkoxyalkyl acrylate monomers and a water-absorbing material, which enhances adhesion to wet and uneven surfaces.

Benefits of technology

The composition achieves both strong adhesive strength and releasability on wet surfaces with unevenness, ensuring effective temporary protection during construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628012000001
    Figure 0007628012000001
  • Figure 0007628012000002
    Figure 0007628012000002
  • Figure 0007628012000003
    Figure 0007628012000003
Patent Text Reader

Abstract

To provide an adhesive composition or the like that has adhesion to a wet surface, particularly a wet surface having irregularities, and also has re-peelability therefrom.SOLUTION: An adhesive composition contains a polymer (A) having an alkoxyalkyl aceylate monomer-derived constitutional unit and a water-absorbing material (B).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel pressure-sensitive adhesive composition. [Background technology]

[0002] When paving roads with asphalt, the asphalt may adhere to the curbs and cause dirt. To prevent this, it is known to attach protective sheets based on films to the curbs to protect them.

[0003] Patent Document 1 describes an adhesive tape for concrete curing in which an acrylic adhesive layer is laminated on at least one surface of a support, the acrylic adhesive layer containing an acrylic polymer (A) in which polar groups are localized within the molecule, thereby providing an adhesive tape for concrete curing that has good retention when applied to concrete and leaves little adhesive residue when removed from the concrete after a certain period of time has passed since application. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-65186 A Summary of the Invention [Problem to be solved by the invention]

[0005] For temporary protection of buildings and civil engineering structures during construction, curing sheets are sometimes used outdoors, and the adherends tend to become wet during rainy days, after rain, when water leaks, or when condensation occurs, so there is a need to improve the adhesive strength to wet surfaces. However, the above-mentioned conventional techniques have a problem in that they are unable to obtain excellent adhesive strength to wet surfaces, particularly when the adherend has a rough surface that is not smooth, such as exposed mortar or concrete. An object of the present invention is to provide a novel pressure-sensitive adhesive composition and the like. Another object of the present invention is to provide a pressure-sensitive adhesive composition and the like which can achieve both adhesive strength and removability on a wet surface, particularly on a wet surface having irregularities. [Means for solving the problem]

[0006] The inventors conducted research in consideration of the above-mentioned problems and discovered that a composition containing a polymer having a structural unit derived from an acrylic acid alkoxyalkyl ester monomer and a water-absorbent material is effective in achieving both adhesive strength to wet surfaces and removability, and thus completed the present invention. That is, the above object can be achieved by a pressure-sensitive adhesive composition containing a polymer having structural units derived from an acrylic acid alkoxyalkyl ester monomer and a water-absorbing material. Effect of the Invention

[0007] According to the present invention, a novel pressure-sensitive adhesive composition and the like can be provided. The pressure-sensitive adhesive composition of the present invention makes it possible to achieve both adhesive strength and removability on wet surfaces, particularly on wet surfaces having irregularities. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below. The pressure-sensitive adhesive composition of the present invention contains a polymer (A) having a structural unit derived from an acrylic acid alkoxyalkyl ester monomer (hereinafter sometimes referred to as polymer (A)) and a water-absorbing material (B) (hereinafter sometimes referred to as water-absorbing material). [Polymer having structural units derived from alkoxyalkyl acrylate monomer] The polymer (A) of the present invention has structural units derived from an alkoxyalkyl acrylate monomer.

[0009] The structural unit derived from an acrylic acid alkoxyalkyl ester monomer refers to a structural unit in which at least one carbon-carbon double bond of an acrylic acid alkoxyalkyl ester monomer is replaced with a carbon-carbon single bond. The structural unit derived from an acrylic acid alkoxyalkyl ester monomer may have the same structure as that in which at least one carbon-carbon double bond of an acrylic acid alkoxyalkyl ester monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of an acrylic acid alkoxyalkyl ester monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization. For example, when the acrylic acid alkoxyalkyl ester monomer is 2-methoxyethyl acrylate, CH 2 =CH(COOCH 2 CH 2 OCH 3 ), the structural unit derived from 2-methoxyethyl acrylate is -CH2-CH(COOCH 2 CH 2 OCH 3 )-, can be expressed as:

[0010] The structural unit derived from an alkoxyalkyl acrylate monomer is preferably a structural unit represented by the following general formula (1).

[0011] [ka] (In the general formula (1), X is an alkylene group having 2 to 4 carbon atoms, Y is an alkyl group having 1 to 10 carbon atoms, and n is an integer of 1 to 10.)

[0012] The structural unit derived from the alkoxyalkyl acrylate monomer preferably has a structure represented by the general formula (1), for example, a structure represented by the following general formula (2):

[0013] [ka] (In the general formula (2), X, Y, and n are the same as those in the general formula (1)). The alkoxyalkyl acrylate monomer represented by the following formula (1) can be polymerized to introduce the alkoxyalkyl acrylate monomer into the polymer (A). The structural unit derived from the alkoxyalkyl acrylate monomer is preferably a structure formed by polymerizing an alkoxyalkyl acrylate monomer, but may be formed by a method other than polymerizing an alkoxyalkyl acrylate monomer, so long as it has the same structure as the structure formed by polymerizing an alkoxyalkyl acrylate monomer.

[0014] In the general formula (1), X may be an alkylene group having 2 to 4 carbon atoms, and may be a linear alkylene group or a branched alkylene group. Examples of X include an ethylene group, a propane-1,3-diyl group, a butane-1,4-diyl group, a propane-1,2-diyl group, a butane-1,2-diyl group, and a butane-1,3-diyl group. More preferably, X is an ethylene group, a propylene group (propane-1,2-diyl group), a trimethylene group (propane-1,3-diyl group), and a butylene group (butane-1,3-diyl group). In the general formula (1), Y is not particularly limited as long as it is an alkyl group having 1 to 10 carbon atoms, and may be a linear alkyl group, a branched alkyl group, or an alkyl group containing a ring. Examples of Y include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group. More preferably, Y is a methyl group, an ethyl group, or a butyl group. In general formula (1), n ​​is not particularly limited as long as it is an integer of 1 to 10, but is more preferably an integer of 1 to 3, and further preferably an integer of 1 to 2. When n is an integer of 2 or more, the multiple Xs contained in -(XO-)n- may be the same or different.

[0015] The alkoxyalkyl acrylate monomer represented by the general formula (2) may be used alone or in combination of two or more. The acrylic acid alkoxyalkyl ester monomer is not particularly limited, and examples thereof include 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-propoxyethyl acrylate, 2-butoxyethyl acrylate, 3-methoxypropyl acrylate, 3-ethoxypropyl acrylate, 4-methoxybutyl acrylate, 4-ethoxybutyl acrylate, 2-methoxytriethylene glycol acrylate, etc. Among them, the acrylic acid alkoxyalkyl ester is more preferably 2-methoxyethyl acrylate or 2-ethoxyethyl acrylate from the viewpoint of the cohesive strength, adhesive strength, tack, etc. of the resulting adhesive layer.

[0016] The proportion of the structural units derived from the acrylic acid alkoxyalkyl ester monomer in all structural units of the polymer (A) of the present disclosure is not particularly limited, but from the viewpoint of adhesion to uneven wet surfaces, the lower limit proportion is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 65 mass% or more, and particularly preferably 70 mass% or more, and the upper limit proportion is preferably 99.5 mass% or less, more preferably 99.0 mass% or less, even more preferably 98.5 mass% or less, and particularly preferably 98 mass% or less. The polymer (A) of the present disclosure may have structural units other than structural units derived from alkoxyalkyl acrylate monomers.

[0017] As structural units other than those derived from alkoxyalkyl acrylate monomers, structural units derived from carboxyl group-containing monomers and structural units derived from hydroxyl group-containing monomers may be contained.

[0018] In the polymer (A) of the present disclosure, the structural unit derived from a carboxyl group-containing monomer can be introduced into the polymer (A), for example, by polymerizing a carboxyl group-containing monomer. As the carboxyl group-containing monomer, a monomer containing a carboxyl group and a polymerizable double bond can be suitably used. Examples of such monomers include acrylic acid, methacrylic acid, itaconic acid, maleic acid, crotonic acid, etc. These carboxyl group-containing monomers may be used alone or in combination of two or more.

[0019] When the polymer (A) contains a structural unit derived from a carboxyl group-containing monomer, the ratio of the structural unit derived from the carboxyl group-containing monomer to the total structural units of the polymer (A) is not limited thereto, but is preferably 0.1% by mass or more as a lower limit ratio, more preferably 0.2% by mass or more, even more preferably 0.3% by mass or more, particularly preferably 0.5% by mass or more, and is preferably 10% by mass or less as an upper limit ratio, more preferably 8% by mass or less, even more preferably 7% by mass or less, particularly preferably 6% by mass or less. If the ratio of the structural unit derived from the carboxyl group-containing monomer to the total structural units of the polymer (A) is 0.1% by mass or more, it is preferable because the cohesiveness of the adhesive is improved. In addition, if the ratio is 10% by mass or less, it is preferable because the wettability and tackiness to the adherend are improved.

[0020] The structural unit derived from the hydroxyl group-containing monomer can be, for example, obtained by polymerizing a hydroxyl group-containing monomer. By this, it can be introduced into the polymer (A). As the hydroxyl group-containing monomer, a monomer containing a hydroxyl group and a polymerizable double bond can be suitably used. Examples of such monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; crosslinkable monomers containing alcoholic hydroxyl groups such as vinyl alcohol, allyl alcohol, caprolactone-modified 2-hydroxyethyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, and 2-acryloyloxyethyl-2-hydroxyethylphthalic acid; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; and the like. These hydroxyl group-containing monomers may be used alone or in combination of two or more. Among them, the hydroxyl group-containing monomer is more preferably a hydroxyalkyl(meth)acrylate having an alkyl group of 2 to 8 carbon atoms from the viewpoint of reactivity with a crosslinking agent.

[0021] When the polymer (A) contains a structural unit derived from a hydroxyl group-containing monomer, the ratio of the structural unit derived from the hydroxyl group-containing monomer to the total structural units of the polymer (A) is not limited thereto, but is preferably 0.01% by mass or more as a lower limit ratio, more preferably 0.05% by mass or more, even more preferably 0.07% by mass or more, and particularly preferably 0.1% by mass or more, and more preferably 5.0% by mass or less as an upper limit ratio, more preferably 4.0% by mass or less, even more preferably 3.0% by mass or less, and particularly preferably 2.0% by mass or less. If the ratio of the structural unit derived from the hydroxyl group-containing monomer to the total structural units of the polymer (A) is 0.01% by mass or more, it is preferable because it behaves as a crosslinking point. In addition, if the ratio is 5.0% by mass or less, it is preferable because it is easy to balance the pot life and physical properties after mixing with a crosslinking agent.

[0022] Alternatively, the polymer (A) may be a polymer in which the proportion of structural units derived from the acrylic acid alkoxyalkyl ester monomers is 50 to 99.5 mass%, the proportion of structural units derived from carboxyl group-containing monomers is 0.1 to 10 mass%, and the proportion of structural units derived from hydroxyl group-containing monomers is 0.01 to 0.5 mass%, based on the total structural units of the polymer (A).

[0023] In the polymer (A) of the present disclosure, as a structural unit other than the structural unit derived from the alkoxyalkyl acrylate monomer, the other monomer is not particularly limited, and a monomer usually used in a (meth)acrylic adhesive, such as an alkyl(meth)acrylate, can be used. The alkyl group of the alkyl(meth)acrylate is preferably an alkyl group having 1 to 20 carbon atoms. The alkyl group may be any of a linear, branched, and alicyclic alkyl group. Specific examples of alkyl (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, 2-ethylhexyl carbitol (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, etc. These alkyl (meth)acrylic acid esters may be used alone or in combination of two or more. The proportion of structural units derived from alkyl (meth)acrylate ester in all structural units of the polymer (A) is preferably 45 mass % or less, and more preferably 40 mass % or less.

[0024] As the other monomer, a vinyl-based compound can be used other than the alkyl (meth)acrylic acid ester. Examples of the vinyl-based compound include aromatic unsaturated hydrocarbon compounds such as styrene and α-methylstyrene; vinyl esters of monocarboxylic acids having 1 to 5 carbon atoms such as vinyl acetate and vinyl propionate; dimethyl (meth)acrylamide, diethyl (meth)acrylamide, isopropyl (meth)acrylamide, (meth)acryloylmorpholine, N-vinylpyrrolidone, and (meth)acrylonitrile. These vinyl-based compounds may be used alone or in combination of two or more. The proportion of the structural units derived from the vinyl-based compound in the total structural units of the polymer (A) is preferably 20% by mass or less, more preferably 10% by mass or less.

[0025] The polymer (A) of the present disclosure may have a functional group (such as a hydroxyl group or an acid group). The embodiment having a functional group is not particularly limited, but may have, for example, a structural unit derived from a monomer having a functional group. That is, the polymer (A) may contain a monomer having a functional group (referred to as a functional group α). When the polymer (A) has a structural unit derived from a monomer having such a functional group α, it is easy to efficiently form a crosslinked structure depending on the type of crosslinking agent (combination with the functional group β of the crosslinking agent) described later.

[0026] The functional group α can be appropriately selected depending on the combination with a crosslinking agent described below or the combination with the functional group β, and examples thereof include an acid group (such as a carboxyl group), an isocyanate group, an oxazoline group, an oxazolidine group, a hydrazino group, an epoxy group, an amino group, a hydroxyl group, and a mercapto group. The monomer having the functional group α may have these functional groups alone or in combination of two or more kinds. Among these functional groups, acid groups, oxazoline groups, hydrazino groups, hydroxyl groups, etc. are representative. In particular, the functional group α may be a functional group that can react (crosslink) with at least a functional group (functional group β) possessed by the crosslinking agent. For example, when the crosslinking agent has an epoxy group, a monomer having an acid group, a hydroxyl group, etc. may be suitably used. Specific examples of monomers having a functional group α include carbonyl group-containing monomers, acid group-containing monomers, oxazoline group-containing monomers, and hydroxyl group-containing monomers.

[0027] The lower limit of the weight average molecular weight of the polymer (A) of the present disclosure is preferably 100,000 or more, more preferably 200,000 or more, and even more preferably 300,000 or more, and the upper limit of the weight average molecular weight is preferably 2 million or less, more preferably 1.5 million or less, and even more preferably 1.2 million or less. If the weight average molecular weight is 100,000 or more, it is preferable from the viewpoint of the cohesiveness of the polymer. If the weight average molecular weight is 2 million or less, it is preferable from the viewpoint of the handleability and wettability to the adherend. Here, in this specification, the weight average molecular weight is a molecular weight measured in terms of polystyrene using gel permeation chromatography (GPC). More specifically, the weight average molecular weight can be a value converted by standard polystyrene [manufactured by Tosoh Corporation] using a measuring device, product number: HLC-8320GPC manufactured by Tosoh Corporation, and a separation column, product number: TSKgel Super HZM-M manufactured by Tosoh Corporation.

[0028] In the polymer (A) of the present disclosure, the content ratio of components having a weight average molecular weight of 10,000 or less is preferably 10 area% or less, more preferably 5 area% or less, even more preferably 2 area% or less, preferably 0.1 area% or more, more preferably 0.3 area% or more, and more preferably 0.5 area% or more. The content ratio of components having a weight average molecular weight of 10,000 or less can be obtained, for example, from the area ratio obtained from a GPC elution curve. Specifically, the ratio of the area from the point on the baseline at the elution time at which the weight average molecular weight becomes 10,000 to the end point of the elution curve in the area from the start point to the end point of the elution curve can be obtained as the content (mass%) of components having a weight average molecular weight of 10,000 or less. By the content ratio of components having a weight average molecular weight of 10,000 or less in the polymer (A) being within the above range, it is possible to achieve both adhesion to a surface having unevenness and removability. For the polymer (A) for which it is not appropriate to measure under the above conditions, for example, the weight average molecular weight may be measured under the above conditions with appropriate, minimal changes.

[0029] The glass transition temperature of the polymer (A) of the present disclosure may be, from the viewpoints of the adhesiveness, tackiness, etc. of the adhesive composition and the adhesive composition for a concrete curing adhesive tape, preferably -100°C or more as the lower limit, more preferably -90°C or more, and even more preferably -80°C or more as the upper limit, preferably -10°C or less, more preferably -20°C or less, and even more preferably -30°C or less. The glass transition temperature of the polymer (A) is calculated by the following formula using the glass transition temperatures of the homopolymers of the monomers (each monomer) used in the monomer components constituting the polymer (A): 1 / Tg=Σ(Wm / Tgm) / 100 (In the formula, Wm represents the content (mass%) of monomer m in the monomer components constituting the polymer, and Tgm represents the glass transition temperature (absolute temperature: K) of a homopolymer of monomer m.) The temperature may be determined based on the Fox formula:

[0030] In addition, for monomers whose glass transition temperature is unknown, such as special monomers and polyfunctional monomers, the glass transition temperature may be determined using only monomers whose glass transition temperatures are known. The glass transition temperatures of the homopolymers are, for example, 106°C for a homopolymer of acrylic acid, 130°C for a homopolymer of methacrylic acid, -41°C for a homopolymer of ω-carboxypolycaprolactone acrylate (manufactured by Toa Gosei Co., Ltd., trade name: Aronix (registered trademark) M-5300), -70°C for a homopolymer of 2-ethylhexyl acrylate, -56°C for a homopolymer of n-butyl acrylate, 10°C for a homopolymer of methyl acrylate, 105°C for a homopolymer of methyl methacrylate, -24°C for a homopolymer of ethyl acrylate, and -41°C for a homopolymer of n-butyl acrylate. For homopolymers, the temperatures are -54°C, for homopolymers of n-butyl methacrylate, -20°C, for homopolymers of n-octyl acrylate, -80°C, for homopolymers of isooctyl acrylate, -58°C, for homopolymers of cyclohexyl acrylate, 16°C, for homopolymers of cyclohexyl methacrylate, 83°C, for homopolymers of isobornyl methacrylate, 180°C, for homopolymers of 2-hydroxyethyl acrylate, -15°C, for homopolymers of 2-hydroxyethyl methacrylate, and -32°C for homopolymers of 4-hydroxybutyl acrylate. The glass transition temperature of the polymer (A) can be easily adjusted by appropriately adjusting the types and amounts of the raw material monomers used in preparing the polymer (A).

[0031] [Water absorbent material (B)] The water-absorbent material (B) of the present invention refers to a material capable of absorbing water. The water-absorbing material (B) of the present disclosure is a material having a water absorption rate of 1.0% or more under conditions of 1 atmospheric pressure and 25° C. The water absorption rate is preferably 3.0% or more, more preferably 5.0% or more, and even more preferably 10% or more. The water absorption rate is measured after drying the water-absorbing material at 200° C. and a humidity of 50% for 30 minutes.

[0032] As the water-absorbing material (B), organic water-absorbing materials such as water-absorbing polymers and inorganic water-absorbing materials can be used. The water-absorbing material (B) may be used alone or in combination of two or more kinds.

[0033] Examples of the organic water-absorbing material (B) include polyacrylic acids, water-soluble celluloses, polyvinyl alcohols, polyethylene oxides, starches, alginic acids, chitins, polysulfonic acids, polyhydroxymethacrylates, polyvinylpyrrolidones, polyacrylamides, polyethyleneimines, polyallylamines, polyvinylamines, maleic anhydrides, and copolymers thereof. The organic water-absorbing material (B) is preferably a polymer having a lactam ring structure. The polymer having a lactam ring structure may be a polymer having a structural unit derived from a monomer having a lactam ring structure. Examples of monomers having a lactam ring structure include vinyl lactam monomers such as N-vinyl lactams (eg, N-vinyl pyrrolidone, N-vinyl caprolactam).

[0034] A representative monomer having a lactam ring structure is N-vinylpyrrolidone.When the monomer having a lactam ring structure contains N-vinylpyrrolidone, the proportion of N-vinylpyrrolidone in the monomer having a lactam ring structure may be, for example, 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably about 50% by mass or more, or may be 70% by mass or more [for example, 80% by mass or more, 90% by mass or more, 100% by mass (substantially only N-vinylpyrrolidone)].

[0035] The content of structural units derived from monomers having a lactam ring structure in a polymer having a lactam ring structure may be 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, and particularly preferably about 50% by mass or more, or may be 70% by mass or more (for example, 80% by mass or more, 90% by mass or more, 95% by mass or more, 100% by mass (substantially only monomers having a lactam ring structure), etc.).

[0036] The polymer having a lactam ring structure may have a structural unit other than the structural unit derived from the monomer having a lactam ring structure. Examples of structural units in a polymer having a lactam ring structure other than the structural units derived from a monomer having a lactam ring structure include structural units derived from a (meth)acrylic monomer, a styrene monomer, a vinyl ester, a vinyl ether, an olefin monomer, a halogen-containing monomer, and an unsaturated nitrile.

[0037] The structural unit derived from a (meth)acrylic monomer can be introduced into a polymer having a lactam ring structure by polymerizing a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include aliphatic (meth)acrylic acid esters, aromatic (meth)acrylic acid esters, hydroxyl group-containing (meth)acrylic acid esters, and (meth)acrylic acid.

[0038] The polymer having a lactam ring structure of the present disclosure may contain a structural unit derived from a monomer having a functional group (referred to as functional group γ). When the polymer having a lactam ring structure has a structural unit derived from a monomer having such a functional group γ, it is easy to efficiently form a crosslinked structure depending on the type of crosslinking agent (combination with the functional group β of the crosslinking agent) described below and the type of functional group α of the polymer (A). The organic water-absorbent material may or may not be a crosslinked polymer.

[0039] The water-absorbing material of the present disclosure may be a water-soluble polymer. The water-soluble polymer is a material that has a solubility of 1.0 g or more in 100 g of water under conditions of 1 atmospheric pressure and 25° C. The solubility is preferably 3.0 g or more, more preferably 5.0 g or more, and even more preferably 10 g or more.

[0040] The water-absorbing material of the present disclosure preferably has a weight-average molecular weight of 300 or more, more preferably 500 or more, and even more preferably 10,000 or more, with the upper limit being preferably 2 million or less, more preferably 1.5 million or less, and particularly preferably 1 million or less, 500,000 or less, 300,000 or less, and 100,000 or less in that order. Here, in this specification, the weight-average molecular weight is a molecular weight calculated as polysulfone measured using gel permeation chromatography (GPC). More specifically, the weight-average molecular weight can be a value calculated using standard polysulfone (manufactured by Tosoh Corporation) using a measuring device manufactured by Tosoh Corporation, product number: HLC-8320GPC, and a separation column manufactured by Tosoh Corporation, product number: TSKgel Super HZM-M.

[0041] In the water-absorbing material of the present disclosure, the content ratio of components having a weight-average molecular weight of 200,000 or less is preferably 50% by area or more, more preferably 70% by area or more, and even more preferably 90% by area or more. The content ratio of components having a weight-average molecular weight of 200,000 or less can be obtained, for example, from the area ratio obtained from the GPC elution curve. Specifically, the ratio of the area from the point on the baseline at the elution time at which the weight-average molecular weight becomes 200,000 to the end point of the elution curve in the area from the start point to the end point of the elution curve can be obtained as the content (mass%) of components having a weight-average molecular weight of 200,000 or less. By having the content ratio of components having a weight-average molecular weight of 200,000 or less in the water-absorbing material within the above range, it is expected that the adhesion strength to a surface having unevenness will be improved.

[0042] When the water-absorbing material of the present disclosure is a crosslinked material, the average particle size after drying under conditions of 200°C and 30 minutes is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, while it is preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. Examples of inorganic water-absorbent materials include silica gel and inorganic polymers such as Sumecton SA manufactured by Kunimine Industries Co., Ltd.

[0043] [Adhesive composition] The content of the polymer (A) in the pressure-sensitive adhesive composition of the present disclosure, relative to the total amount of the components of the pressure-sensitive adhesive composition excluding the solvent, taken as 100 mass%, is preferably 60 mass% or more as a lower limit, more preferably 70 mass% or more, and even more preferably 80 mass% or more as an upper limit, and is preferably 99.5 mass% or less, more preferably 99 mass% or less, and even more preferably 98 mass% or less. When the content of the polymer (A) in the pressure-sensitive adhesive composition is 60 mass% or more, it is expected that a pressure-sensitive adhesive composition can be realized that has both adhesive strength and removability to wet surfaces, particularly to wet surfaces having unevenness.

[0044] In the pressure-sensitive adhesive composition of the present disclosure, the content of structural units derived from acrylic acid alkoxyalkyl ester monomers is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the total amount of components of the pressure-sensitive adhesive composition excluding the solvent being 100 mass%, and is preferably 99.5 mass% or less, more preferably 99 mass% or less, and even more preferably 98 mass% or less.

[0045] The content of the water-absorbing material (B) in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but from the viewpoint of the ability to absorb and remove moisture from the adherend, the content is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, and even more preferably 1 mass % or more, based on the total components of the pressure-sensitive adhesive composition excluding the solvent, i.e., when the total amount of the components of the pressure-sensitive adhesive composition excluding the solvent is taken as 100 mass %. In the pressure-sensitive adhesive composition of the present disclosure, the ratio of the water-absorbing material (B) to the total amount of the polymer (A) having a structural unit derived from an acrylic acid alkoxyalkyl ester monomer and the water-absorbing material (B) is preferably 0.5 mass% or more, more preferably 1.0 mass% or more, and even more preferably 1.5 mass% or more, and is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 15 mass% or less.

[0046] The molar ratio of the structural units derived from an acrylic acid alkoxyalkyl ester monomer to the structural units derived from a monomer having a lactam ring structure in the pressure-sensitive adhesive composition of the present disclosure may be preferably 99.5 / 0.5 to 85 / 15, more preferably 99 / 1 to 88 / 12, and even more preferably 98.5 / 1.5 to 90 / 10. By having the molar ratio of the structural units derived from an acrylic acid alkoxyalkyl ester monomer to the structural units derived from a monomer having a lactam ring structure within the above range, it is expected to provide a pressure-sensitive adhesive composition that can achieve both adhesive strength and removability on wet surfaces, particularly on wet surfaces having unevenness.

[0047] The pressure-sensitive adhesive composition of the present disclosure may contain a crosslinking agent. Such a crosslinking agent may be capable of crosslinking the polymer (A) (and further the water-absorbing material (B)). From this viewpoint, the crosslinking agent may have a functional group (functional group β), and in particular, such a functional group may be a functional group (functional group β) that can react (crosslink) with the functional group α (and further with the functional group γ). Examples of such a functional group β include the functional groups exemplified in the section on the functional group α (and the functional group γ), such as an acid group (such as a carboxyl group), a hydrazino group, an oxazoline group, an epoxy group, an isocyanate group, and an amino group.

[0048] The combination of the functional group α (and further the functional group γ) and the functional group β is not particularly limited, and examples thereof include an epoxy group and a hydroxyl group (hydroxyl group), an epoxy group and an acid group (such as a carboxyl group), an epoxy group and an amino group, a carbonate group and an acid group (such as a carboxyl group), a hydroxyl group and an alkoxycarbonyl group, a hydroxyl group and an isocyanate group, a hydroxyl group and a carboxylic anhydride group, an acetoacetoxy group and an isocyanate group, an oxazoline group and a carboxyl group, a hydroxyl group and a carboxylic anhydride group, an oxazolidine group and an isocyanate group or a carboxylic anhydride group, a hydrazino group and a carbonyl group, etc. These may be combined alone or in combination of two or more. In the crosslinking agent, the number of such functional groups (functional group β) may be 1, but in particular, may be 2 or more (plural). Typically, the crosslinking agent may contain a polyfunctional compound (a compound having 2 or more functional groups β). In such a crosslinking agent (polyfunctional compound), the number of functional groups (functional group β) may be 2 or more, and for example, in the case of a low molecular weight (non-polymer type or non-resin type) polyfunctional compound, the number may be 2 to 10, preferably 2 to 6, and more preferably 2 to 4 (for example, 2).

[0049] Representative crosslinking agents include hydrazine-based crosslinking agents (compounds having multiple hydrazino groups), oxazoline-based crosslinking agents, isocyanate-based crosslinking agents, amine-based crosslinking agents, and epoxy-based crosslinking agents. The crosslinking agents may be used alone or in combination of two or more kinds. When a crosslinking agent is used, the proportion of the crosslinking agent used depends on the type of crosslinking agent, the type of its functional group, and the composition. The amount can be appropriately selected depending on the desired viscosity of the product, and may be, for example, 0.001 parts by mass or more, preferably 0.005 parts by mass or more, and more preferably 0.01 parts by mass or more, per 100 parts by mass of the polymer (A) (and further the water-absorbing material (B)). The upper limit of the proportion of the crosslinking agent used is not particularly limited and can be selected depending on the type of the crosslinking agent, and may be, for example, 10 parts by mass, 5 parts by mass, 3 parts by mass, 2 parts by mass, 1 part by mass, 0.5 parts by mass, 0.3 parts by mass, 0.2 parts by mass, 0.1 parts by mass, etc., relative to 100 parts by mass of the polymer (A) (and further the water-absorbing material (B)).

[0050] The pressure-sensitive adhesive composition of the present disclosure may contain, as necessary, a viscosity modifier, a plasticizer, a filler, a softener, a surfactant (emulsifier), an anti-aging agent, a leveling agent, an antioxidant, a light stabilizer, an antifoaming agent, a release modifier, a polymerization inhibitor, a tackifier, and the like, within a range that does not impair the effects of the present invention. The proportion of other components used can be appropriately selected depending on the type and application of the components. The adhesive composition of the present disclosure may contain, or may not substantially contain, a moisture-curing component (such as an isocyanate compound, an alkoxysilyl group-containing polymer, a cyanoacrylate compound, or a urethane-based compound. The adhesive composition of the present disclosure can exhibit or demonstrate sufficient adhesion (adhesion to a wet surface) even if it does not contain such a component.

[0051] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent, or may be a solvent-based composition (non-aqueous solvent-based composition). Examples of the organic solvent of the present disclosure include aromatic hydrocarbons (e.g., benzene, toluene, xylene, ethylbenzene, etc.), aliphatic or alicyclic hydrocarbons (e.g., hexane, heptane, cyclohexane, methylcyclohexane, etc.), halogenated solvents (e.g., chloroform, methylene chloride, carbon tetrachloride, etc.), ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), esters (e.g., aliphatic esters such as methyl acetate, ethyl acetate, butyl acetate, etc.), ethers [e.g., linear ethers (e.g., diethyl ether, etc.), cyclic ethers (e.g., tetrahydrofuran, dioxane, etc.)], nitrogen-containing solvents {e.g., linear amides [e.g., N-substituted linear amides (N-alkyl-substituted alkanamides such as N,N-dimethylformamide), etc.], cyclic amides (or laminar amides), etc., and the like]. amides such as 2-pyrrolidone, etc.}, alcohols {for example, monools [for example, alkanols (for example, C1-6 alkanols such as methanol, ethanol, isopropanol, etc., preferably C1-4 alkanols), etc.], polyols [for example, alkanediols (for example, C2-6 alkanediols such as ethylene glycol, propylene glycol, etc., preferably C2-4 alkanediols), polyols having three or more hydroxyl groups (for example, glycerin, etc.)], etc.}, glycol ethers (for example, monoalkyl ethers of alkanediols or polyalkanediols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, diethylene glycol monoethyl ether, etc.), etc.].

[0052] The boiling point (boiling point at normal pressure or atmospheric pressure) of the organic solvent of the present disclosure is not particularly limited, but from the viewpoint of forming a pressure-sensitive adhesive layer, it may be a relatively low boiling point, for example, 180°C or less, preferably 150°C or less, and more preferably 130°C or less. The solvent may contain an organic solvent (sometimes referred to as organic solvent B1) capable of dissolving at least the water-absorbing material (B) (particularly a polymer having a lactam ring structure). The organic solvent of the present disclosure may be a hydrophilic or water-soluble solvent, depending on the type of water-absorbing material, etc. The solubility of such a solvent in water (20°C) may be, for example, 10 g / 100 g or more, preferably 20 g / 100 g or more, and more preferably 50 g / 100 g or more, and may be a solvent that is miscible with water (optionally miscible) (a good solvent for water).

[0053] The organic solvent of the present disclosure may contain an organic solvent capable of dissolving the polymer (A) (sometimes referred to as organic solvent A1). Such organic solvent A1 may be a hydrophobic solvent, depending on the type of the polymer (A). The solubility of such a solvent in water (20°C) may be, for example, 10 g / 100 g or less (for example, less than 10 g / 100 g), or may be a solvent that is substantially insoluble in water (a poor solvent for water).

[0054] The organic solvent A1 may be a solvent common to the organic solvent B1, i.e., an organic solvent capable of dissolving both the water-absorbing material (B) (particularly, a polymer having a lactam ring structure) and the polymer (A), but may generally be a solvent that does not dissolve (or is difficult to dissolve) the water-absorbing material (B) (particularly, a polymer having a lactam ring structure). The organic solvents may be used alone or in combination of two or more kinds.

[0055] Specific examples of the organic solvent B1 include, depending on the type of water-absorbing material (B), alcohols (e.g., methanol, ethanol, isopropanol, ethylene glycol, glycerin, etc.), halogen-based solvents (e.g., chloroform, etc.), and amides [e.g., chain amides (e.g., N,N-dimethylformamide), cyclic amides (or lactams, e.g., 2-pyrrolidone, etc.)] from among the above-listed solvents. Specific examples of the organic solvent A1 include aromatic hydrocarbons (e.g., toluene, xylene, etc.), aliphatic esters (e.g., ethyl acetate, butyl acetate, etc.), etc., depending on the type of polymer (A). From the viewpoint of the solubility of the water-absorbing material (B), particularly the polymer having a lactam ring structure, alcohols are preferred, methanol, ethanol, and isopropanol are more preferred, and methanol and isopropanol are even more preferred. The organic solvent B1 and the organic solvent A1 may each be used alone or in combination of two or more kinds.

[0056] The pressure-sensitive adhesive composition of the present disclosure can efficiently balance adhesion to wet surfaces and removability by selecting the type of organic solvent (and further the combination of organic solvents and the form in which each component is present in the composition). The adhesive composition of the present disclosure preferably contains a solvent, and the solvent often contains at least an organic solvent. In such a solvent containing an organic solvent, the ratio of the organic solvent to the entire solvent can be selected from, for example, 10% by mass or more, and may be usually 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, or may be 80% by mass or more [for example, 85% by mass or more, 90% by mass or more, 95% by mass or more, 100% by mass (substantially only organic solvent), etc.].

[0057] The pressure-sensitive adhesive composition of the present disclosure may contain water as long as it does not impede the object of the present invention, but even if it does contain water, it is preferable that the amount is relatively small. The ratio of water to the entire solvent can be selected from a range of 90% by mass or less, and may be usually 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less, or may be 20% by mass or less [for example, 15% by mass or less, 10% by mass or less, 5% by mass or less, 0% by mass (substantially no water), etc.].

[0058] When the solvent contains organic solvent B1, the ratio of organic solvent B1 to the entire solvent may be, for example, 0.5 mass% or more (e.g., 1 mass% or more, 1.5 mass% or more, 2 mass% or more, 2.5 mass% or more), preferably 3 mass% or more (e.g., 3.5 mass% or more, 4 mass% or more), more preferably 5 mass% or more (e.g., 5.5 mass% or more, 6 mass% or more, 6.5 mass% or more, 7 mass% or more), 8 mass% or more (e.g., 8.5 mass% or more, 9 mass% or more, 9.5 mass% or more), 10 mass% or more, etc. When the solvent contains organic solvent A1, the ratio of organic solvent A1 to the entire solvent may be, for example, 99.5 mass% or less (e.g., 99 mass% or less, 98.5 mass% or less, 98 mass% or less, 97.5 mass% or less), preferably 97 mass% or less (e.g., 96.5 mass% or less, 96 mass% or less, 95.5 mass% or less), more preferably 95 mass% or less (e.g., 94.5 mass% or less, 94 mass% or less, 93.5 mass% or less, 93 mass% or less, 92.5 mass% or less), more preferably 92 mass% or less (e.g., 91.5 mass% or less, 91 mass% or less, 90.5 mass% or less), or may be 90 mass% or less, etc. When the solvent contains an organic solvent A1 and an organic solvent B1, the ratio thereof (organic solvent A1 / organic solvent B1) (mass ratio) may be about 99.9 / 0.1 to 1 / 99 (e.g., 99.5 / 0.5 to 5 / 95), preferably 99 / 1 to 10 / 90 (e.g., 98.5 / 1.5 to 15 / 85), more preferably 98 / 2 to 20 / 80 (e.g., 97.5 / 2.5 to 25 / 75), particularly 97 / 3 to 30 / 70 (e.g., 96.5 / 3.5 to 40 / 60), or may be 99 / 1 to 50 / 50, 99 / 1 to 55 / 45, 98 / 2 to 60 / 40, 97 / 3 to 65 / 35, 96 / 4 to 70 / 30 (e.g., 95 / 5 to 80 / 20), or the like.

[0059] The pressure-sensitive adhesive composition of the present disclosure may be in a form in which the polymer (A) and the water-absorbing material (B) are dissolved or dispersed in a solvent, and it is preferable that at least the water-absorbing material (B) (particularly the polymer having a lactam ring structure) is dissolved in the solvent. The presence of a polymer having a lactam ring structure (and furthermore polymer (A)) in such a dissolved state makes it easy to achieve both adhesive strength and removability on wet surfaces, particularly on wet surfaces having irregularities. In addition, such a dissolved state may be sufficient if the polymer having a lactam ring structure (and furthermore the polymer (A)) is substantially dissolved, and may be completely dissolved or may remain partially undissolved.

[0060] In such a composition (a composition having residual dissolution), the proportion of undissolved solids (e.g., the water-absorbing material (B) and / or the polymer (A)) may be 10 mass % or less, 8 mass % or less, 5 mass % or less, 3 mass % or less, 2 mass % or less, 1 mass % or less, 0.5 mass % or less, etc., relative to the total amount of solids (the water-absorbing material (B) and the polymer (A)). In the pressure-sensitive adhesive composition of the present disclosure, the proportion of the solid content (or non-volatile content, for example, the total amount of the polymer (A) and the water-absorbing material (B)) may be 10 mass % or more, preferably 20 mass % or more, and more preferably 30 mass % or more, relative to the entire composition, and may be 80 mass % or less (for example, 70 mass % or less, 60 mass % or less). The viscosity of the pressure-sensitive adhesive composition of the present disclosure may be, for example, 300 mPa·s or more, preferably 500 mPa·s or more, and more preferably 1000 mPa·s or more, and may be 20000 mPa·s or less (e.g., 15000 mPa·s or less, 10000 mPa·s or less).

[0061] The method for producing the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, and the composition can be obtained by mixing the respective components (polymer (A), water-absorbing material (B), solvent, etc.). In particular, in the present invention, the water-absorbing material (B) and the organic solvent B1 (which dissolves the water-absorbing material (B)) are The composition may be obtained by mixing a composition containing a possible organic solvent B1) (which may be referred to as composition B) with the polymer (A). The polymer (A) and the water-absorbing material (B) usually do not mix (become compatible) easily, but by going through such a specific process (a process of preparing composition B in advance), they can be mixed (become compatible) relatively uniformly.

[0062] Therefore, the present invention includes such composition B. Such composition B can be said to be a composition for obtaining a composition (adhesive composition) containing the polymer (A), the water-absorbing material (B) and a solvent. In such a composition B, the organic solvent B1 (solvent containing the organic solvent B1) can be said to be a useful component for uniformly mixing (or dissolving) the polymer (A) and the water-absorbing material (B). Therefore, the present invention includes an agent for improving or enhancing the compatibility of the water-absorbing material (B) with the polymer (A), which contains the organic solvent B1.

[0063] Such organic solvent B1 may be any of the solvents exemplified above (organic solvent B1). However, from the viewpoint of compatibility with the adhesive layer, it may be preferable to use alkanols (e.g., lower or C1-4 alkanols such as methanol, ethanol, isopropanol, etc.; C2-4 alkanediols such as ethylene glycol; glycerin, etc.), cyclic amides (2-pyrrolidone, etc.), etc.

[0064] In the composition B, the water-absorbing material (B) is usually dissolved (in a dissolved state) in a solvent (solvent containing organic solvent B1), and such a dissolved state may be completely dissolved or may have a part remaining undissolved. When such a part remains undissolved, the proportion of the undissolved water-absorbing material (B) may be 10% by mass or less, 8% by mass or less, 5% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, etc., based on the total amount of the water-absorbing material (B). In composition B, the proportion of the water-absorbing material (B) is not particularly limited, and may be, for example, 1 mass% or more (e.g., 3 mass% or more), preferably 5 mass% or more (e.g., 7 mass% or more), and more preferably 10 mass% or more (e.g., 12 mass% or more, 15 mass% or more, etc.), or 90 mass% or less (e.g., 80 mass% or less, 75 mass% or less, 70 mass% or less, 65 mass% or less, 60 mass% or less, 55 mass% or less, 50 mass% or less, 45 mass% or less, etc.).

[0065] The polymer (A) may be mixed directly into the composition B, or may be mixed as a composition containing the polymer (A) and a solvent A1 (an organic solvent A1 capable of dissolving the polymer (A)) (sometimes referred to as composition A). That is, the adhesive composition is prepared by mixing the composition B with the composition A prepared in advance. It may also be manufactured.

[0066] In such composition A, the organic solvent A1 can be selected from the same solvents as those exemplified above (organic solvent A1), etc. In particular, the organic solvent A1 and the organic solvent B1 may be miscible with each other (organic solvent A1 may be a good solvent for organic solvent B1). In the composition A, the polymer (A) is usually dissolved (in a dissolved state) in a solvent (a solvent containing an organic solvent A1), and such a dissolved state may be completely dissolved or may include a part that remains undissolved. When such a part remains undissolved, the proportion of the undissolved polymer (A) may be 10% by mass or less, 8% by mass or less, 5% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, etc., based on the total amount of the polymer (A). In composition A, the proportion of polymer (A) is not particularly limited, and may be, for example, 1 mass% or more (e.g., 3 mass% or more), preferably 5 mass% or more (e.g., 7 mass% or more), and more preferably 10 mass% or more (e.g., 12 mass% or more, 15 mass% or more, etc.), or 90 mass% or less (e.g., 80 mass% or less, 75 mass% or less, 70 mass% or less, 65 mass% or less, 60 mass% or less, 55 mass% or less, 50 mass% or less, 45 mass% or less, etc.).

[0067] In addition, when the composition contains other components (such as a crosslinking agent), the manner and timing of mixing are not particularly limited. For example, the other components may be contained in at least one of composition B and polymer (A) (or composition A), or may be mixed separately with composition B and polymer (A) (or composition A).

[0068] [Adhesive layer] The pressure-sensitive adhesive composition of the present disclosure is suitable for forming a pressure-sensitive adhesive (pressure-sensitive adhesive layer). The method for forming the pressure-sensitive adhesive (pressure-sensitive adhesive layer) is not particularly limited, and for example, the pressure-sensitive adhesive may be formed by applying a pressure-sensitive adhesive composition onto a substrate, or may be formed without using a substrate.

[0069] The substrate is not particularly limited, and examples that can be used include conventionally known papers such as fine paper, craft paper, crepe paper, and glassine paper; plastics such as polyethylene, polypropylene, polyester, polystyrene, polyethylene terephthalate, polyvinyl chloride, and cellophane; and textile products such as woven and nonwoven fabrics. From the viewpoint of maintaining the adhesive strength of the adhesive layer, it is preferable to use, as the substrate, a water-absorbent material or nonwoven fabric that can store the water absorbed after adhering to a wet surface. From the viewpoint of improving conformability to rough surfaces, a highly flexible substrate is preferred. Specifically, substrates based on polyvinyl chloride, woven fabric, and nonwoven fabric, as well as elastic substrates mainly composed of resins such as polyurethane, polyolefin, and olefin-based elastomers, and polyethylene-based foams are preferred. The shape of the substrate may be, for example, a film, a sheet, a tape, a plate, a foam, or the like, but is not particularly limited. The substrate may have a predetermined function (for example, heat insulation, heat shielding, ultraviolet shielding, etc.).

[0070] The pressure-sensitive adhesive layer may be formed on at least one surface (front side) of the substrate, or on both surfaces. When formed on both surfaces, a double-sided tape or the like can be used. In addition, a release paper (release agent layer) or the like may be applied (attached or pasted or provided) to the surface (back side) of the adhesive layer opposite the substrate. Examples of the release paper include sheet (film)-like materials in which a release agent (release agent layer) is applied (or formed) on the surface of paper, synthetic paper, plastic film, etc. By forming the release agent layer, the adhesive surface can be effectively protected or preserved.

[0071] The method for applying the pressure-sensitive adhesive composition is not particularly limited, and any known method such as roll coating, spray coating, dipping, etc. can be used. In this case, any of the following methods can be used: a method for directly applying the pressure-sensitive adhesive composition to a substrate or adherend, a method for applying the pressure-sensitive adhesive composition to release paper or the like, a method for applying the pressure-sensitive adhesive composition to release paper or the like, and a method for pasting or transferring the pressure-sensitive adhesive composition onto a substrate or adherend after applying the pressure-sensitive adhesive composition to release paper or the like.

[0072] The drying temperature after coating of the pressure-sensitive adhesive composition is not particularly limited, but is preferably a temperature at which the solvent in the composition is sufficiently volatilized.

[0073] The adhesive product includes an adhesive (adhesive layer). Depending on the method for forming the adhesive layer, for example, such an adhesive product may be an adhesive sheet, an adhesive label, an adhesive tape, a double-sided tape, etc. Such adhesive products can be used, for example, by contacting (pressing) the adhesive layer with an adherend. If the adhesive product has a release paper, it can be used after peeling it off. The thickness of the adhesive (adhesive layer) can be appropriately selected depending on the application, etc., and is not particularly limited, but may be, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, etc., or 5 mm or less, 3 mm or less, 2 mm or less, etc. When the thickness of the adhesive layer is within the above range, it is expected that the conformability to the rough surface will be improved, high adhesive strength will be obtained even on a rough surface in a wet state, and further that adhesive residue on the adherend will be reduced.

[0074] The pressure-sensitive adhesive layer may be opaque or transparent. The pressure-sensitive adhesive layer contains components (polymer (A), water-absorbing material (B), crosslinking agent, etc.) corresponding to the pressure-sensitive adhesive composition. The form in which these components are contained in the pressure-sensitive adhesive layer is not particularly limited, but may be in a form in which the polymer (A) and the water-absorbing material (B) are relatively uniformly mixed (compatible). It is believed that the adhesion and transparency in a wet state can be more efficiently exhibited or expressed by containing them in such a form. The transparency of the pressure-sensitive adhesive layer does not necessarily correspond to the form in which each component exists in the pressure-sensitive adhesive composition. However, when the water-absorbing material (B) (and further the polymer (A)) is relatively uniformly mixed (dissolved, compatible) in the pressure-sensitive adhesive composition, the transparency of the pressure-sensitive adhesive layer can often be efficiently expressed.

[0075] [Adhesive products] The pressure-sensitive adhesive composition of the present disclosure can be used in various pressure-sensitive adhesive products. Examples of the adhesive product of the present disclosure include adhesive sheets, adhesive labels, adhesive tapes, double-sided tapes, etc. Such adhesive products are manufactured without a substrate, or by forming an adhesive layer on a substrate. More specifically, examples of the adhesive products include adhesive tapes for concrete curing, which are used to fix curing sheets such as polyethylene, polypropylene, polyethylene terephthalate, and nonwoven fabrics on concrete surfaces, and masking tapes (curing tapes for concrete) for protecting concrete, etc., and are effective when used as curing tapes for wet surfaces, particularly wet surfaces with unevenness. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, "parts" means "parts by weight".

[0077] <Measurement method> <Weight average molecular weight> The weight average molecular weight of the polymer was measured under the following conditions. Equipment: Tosoh GPC system HLC-8320GPC ECOSEC Column: One TSKgel Guardcolumn Super HZ-H column, manufactured by Tosoh Corporation, connected in series with three TSKgel Super HZM-H columns Developing solvent: Tetrahydrofuran Flow rate of developing solvent: 0.35 ml / min Detector: RI Standard sample: TSK standard polystyrene (Tosoh Corporation, PS-oligomer kit) Column temperature: 40℃ Sample concentration: 0.2% Sample injection volume: 10 μL

[0078] <Example 1> In a reaction vessel equipped with a cooling tube, a nitrogen gas introduction tube, a thermometer, a dropping funnel and a stirrer, 150 parts of ethyl acetate (parts by weight, the same applies below), 95.5 parts of 2-methoxyethyl acrylate (AME), 2.0 parts of acrylic acid (AA), 2.0 parts of N-vinyl-2-pyrrolidone (NVP), and 0.5 parts of 2-hydroxyethyl acrylate (HEA) were charged (composition 1 in Table 1). Then, 0.1 parts of an azo-based polymerization initiator (manufactured by Japan Finechem Co., Ltd., product name: ABN-E) were added to the reaction vessel, and the mixture was reacted at 80°C for 6 hours in a nitrogen gas atmosphere to obtain an acrylic polymer with a weight average molecular weight of 600,000 and a solid content of 40%. The reaction mixture containing the obtained acrylic polymer was then cooled to room temperature to obtain a pressure-sensitive adhesive composition A. To 100 parts of the adhesive composition A, 20 parts of a methanol solution of polyvinylpyrrolidone (PVP, K-30, manufactured by Nippon Shokubai Co., Ltd.) (4 parts as PVP, 10% by mass as PVP based on the acrylic polymer solid content) and 0.021 parts of Tetrad C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) (0.0525% by mass based on the acrylic polymer solid content) were added to obtain an adhesive composition (B-1) of the present disclosure. The adhesive composition B was applied to a release paper (manufactured by San-A Kaken Co., Ltd., product name: K-80HS) using an applicator, and then dried at a temperature of 80°C for 3 minutes. As a result, an adhesive layer having a thickness of 50 μm was formed on the release paper. A PET (polyethylene terephthalate) film substrate (thickness: 25 μm) was attached to the adhesive layer. After that, aging was performed at 40°C for 120 hours to obtain an adhesive tape of the present disclosure, one side of which is an adhesive surface.

[0079] <Examples 2 to 4> The same reaction and operation as in Example 1 were carried out except that the type and amount of the crosslinking agent were changed as shown in Table 2, to obtain an acrylic polymer, a pressure-sensitive adhesive composition and a pressure-sensitive adhesive tape according to the present disclosure. <Comparative Example 1> Except for changing the monomer composition to composition 3 shown in Table 1, the same reaction and operation as in Example 1 were carried out to obtain an acrylic polymer, a comparative pressure-sensitive adhesive composition, and a pressure-sensitive adhesive tape.

[0080] [Table 1] The abbreviations in Table 1 represent the following compounds. BA: Butyl acrylate 2EHA: 2-Ethylhexyl acrylate AME: 2-Methoxyethyl acrylate NVP: N-vinyl-2-pyrrolidone AA: Acrylic acid HEA: 2-hydroxyethyl acrylate

[0081] The adhesiveness of the pressure-sensitive adhesive tapes obtained in Examples 1 to 4 and Comparative Examples 1 to 3 to a wet lubricated concrete surface and a wet roughened concrete surface was evaluated by the following method.

[0082] <Concrete surface roughness> Smooth concrete surface A mortar board conforming to JIS K5600 was prepared by polishing the surface with sandpaper of grain size 150, and the surface roughness of the mortar board was measured with a laser microscope (VK-9710, manufactured by Keyence Corporation). Arithmetic surface roughness Sa: 4.635μm Root mean square height Sq: 8.702μm Maximum peak height Sp: 128.474μm Maximum valley depth Sv: 160.405μm Rough concrete surface The back surface of a mortar board conforming to JIS K5600 was polished with sandpaper of grain size 150, and the surface roughness of the surface of this mortar board was measured using a sandpaper (VK-9710, manufactured by Keyence Corporation). Arithmetic surface roughness Sa: 20.747μm Root mean square height Sq: 26.399μm Maximum peak height Sp: 162.57μm Maximum valley depth Sv: 203.024μm

[0083] (1) Method for evaluating adhesion to wet concrete surfaces The adhesive tape was cut into a rectangle of 50 mm in length and 25 mm in width to prepare an adhesive tape. A mortar board conforming to JIS standard K5600 was prepared as an adherend. The surface of the mortar board was polished with sandpaper of grain size 150. The polished mortar board was immersed in water for 24 hours, then taken out, and the water on the surface of the mortar board was lightly wiped back and forth with a cloth to prepare a wet adherend. In an atmosphere of 23°C and 50% relative humidity, the release paper of the adhesive tape was peeled off, and the adhesive tape was placed on the mortar surface so that the adhesive surface was in contact with the mortar surface, and a roll with a mass of 2 kg was moved back and forth on the adhesive tape on the mortar surface to attach it to the mortar surface. After leaving it to stand for 25 minutes, the peeling force (adhesive force) was measured when peeled at a peeling angle of 180° and a peeling speed of 300 mm / min, and the adhesion to a wet concrete surface was evaluated.

[0084] (2) Method for evaluating adhesion to wet rough concrete surfaces The evaluation was carried out in the same manner as in (1) above, using rough concrete as the adherend.

[0085] (3) Evaluation of removability of wet rough concrete surfaces In the above (1) and (2), after measuring the peeling force against the dry concrete surface and the wet concrete surface, the state of the adhesive residue on the mortar surface after peeling was visually observed and evaluated according to the following criteria. ○: No adhesive residue ×: Glue remains on part or the entire surface of the sticker

[0086] (4) Evaluation method for retention A stainless steel plate with a polished surface was used as an adherend, and a test piece was placed on the stainless steel plate in an atmosphere with a temperature of 23° C. and a relative humidity of 50%, and the test piece was pressed against the plate by rolling a rubber roller with a mass of 2 kg back and forth once from above the test piece. The pressed test piece was left in an atmosphere with a temperature of 80° C. for 20 minutes, and then a 1 kg weight was attached to the end of the adhesive sheet and hung, and the time required for the adhesive sheet to peel off in the atmosphere was measured.

[0087] [Table 2] The abbreviations in Table 2 represent the following compounds. PVP: Polyvinylpyrrolidone MeOH: Methanol It is clear from Examples 1 to 4 that the pressure-sensitive adhesive tape of the present disclosure obtained from the pressure-sensitive adhesive composition of the present disclosure has excellent adhesion to a rough concrete surface in a wet state.

Claims

1. The adhesive composition contains a polymer (A) having structural units derived from an alkoxyalkyl acrylate ester monomer and a water-absorbing material (B), wherein the structural units derived from the alkoxyalkyl acrylate ester monomer in the polymer (A) account for 60 mass% or more, and the proportion of structural units derived from vinyl compounds other than alkyl (meth)acrylate esters in the total structural units of the polymer (A) is 10 mass% or less, and the water-absorbing material (B) is at least one selected from the group consisting of polyacrylic acids, water-soluble celluloses, polyvinyl alcohols, polyethylene oxides, starches, alginic acids, chitins, polysulfonic acids, polyhydroxymethacrylates, polyvinylpyrrolidones, polyacrylamides, polyethyleneimines, polyallylamines, polyvinylamines, maleic anhydrides, and copolymers thereof.

2. The pressure-sensitive adhesive composition according to claim 1 , wherein the polymer (A) further contains a structural unit derived from a carboxyl group-containing monomer and / or a structural unit derived from a hydroxyl group-containing monomer.

3. The pressure-sensitive adhesive composition according to claim 1 , wherein the water-absorbing material (B) is a water-soluble polymer.

4. The pressure-sensitive adhesive composition according to claim 1, wherein the water-absorbing material (B) is a polymer having a lactam ring structure.

5. The pressure-sensitive adhesive composition according to claim 1, wherein the proportion of the water-absorbing material (B) relative to the total amount of the polymer (A) and the water-absorbing material (B) is 0.5% by mass or more and 30% by mass or less.

6. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the alcohol in the pressure-sensitive adhesive composition is 0.1% by mass or more and 20% by mass or less, and the alcohol is at least one selected from the group consisting of methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, and glycerin.

7. The adhesive composition described in claim 1, wherein the weight average molecular weight of the water-absorbing material (B) is 10,000 or more and 2,000,000 or less.

8. An adhesive layer obtained by applying and drying the adhesive composition according to any one of claims 1 to 7.

9. An adhesive product having an adhesive layer as described in claim 8.

Citation Information

Patent Citations

  • Adhesive sheet for bacterial inspection and method of the inspection

    JP1995051093A

  • Wet-surface-adhering pressure-sensitive adhesive

    JP2002371257A

  • Polymer gel, composition for producing the gel, and adhesive tape

    JP2007262309A

  • Optical device, optical low-pass filter, and solid-state imaging apparatus

    JP2008257215A

  • Laminated antifogging film

    JP2014117839A